The management of delivery with Meconium-stained amniotic fluid - M Ahmad Pour (Babol University of Medical Sciences, 2002)
Aspiration of meconium amniotic fluid may lead to meconium aspiration syndrome with a consequences of significant morbidity and mortality. So perinatal management for prevention of aspiration is very important. Up to now several procedures have been proposed such as selective cesarean section, amnionfusion and tracheobronchial lavage by diluted surfactant, which are not proved to be effective but oropharyngeal and nasopharyngeal suction at the time of the delivery of head before the delivery of shoulders and endotracheal suction after delivery in all depressed infants are the most effective methods. In this study, all these methods were discussed and literatures were reviewed.